Measuring the Effects of a University Planning Decision Aid - Dickmeyer, Nathan (Management Science, 1983)
University administrators involved in budget planning must trade off variables such as faculty size, faculty salary increments, tuition increases, and investment in new initiatives. TRADES is a computer-based, interactive financial model designed to assist in making trade-offs and finding preferred feasible solutions. This paper presents the results of an experiment to test the significance of preference changes resulting from the use of the TRADES model. In this experiment, 38 subjects were divided into two groups, one provided with TRADES and the other only with a printed university projected forecast. The subjects were asked to rank-order 27 different five-year financial policies. The two groups were compared using the preference function assessment technique of Srinivasan and Shocker. The policy preference changes by TRADES users were found to be significantly greater than the preference changes by nonusers. That is, the experience of using the TRADES model to assess budget policy altered the choice of preferred policy. The implication of this experiment is that the preference functions evolve as better understanding is reached of trade-offs and constraints. Therefore, simply eliciting preference functions and then running a model is not sufficient in situations in which learning can take place.